Managing Human Resources for Environmental Sustainability. - Jackson, Susan E. (J-B SIOP Professional Practice Series., 2012)
Managing Human Resources for Environmental Sustainability; The Society for Industrial and Organizational Psychology (SIOP) is the premier membership organization for those practicing industrial and organizational psychology. The Society's mission is to enhance human well-being and performance in organizational and work settings by promoting the science, practice, and teaching of industrial and organizational (I-O) psychology. I-O psychologists apply research that improves the well-being and performance of people and the organizations that employ them. This involves everything from workforce pla.